2002
DOI: 10.1042/0264-6021:3630761
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell growth through inactivation of eukaryotic translation initiation factor 5A (eIF5A) by deoxyspergualin

Abstract: The mechanism of inhibition of cell growth by deoxyspergualin was studied using mouse mammary carcinoma FM3A cells. Results of studies using deoxyspergualin analogues showed that both the guanidinoheptanate amide and glyoxyspermidine moieties of deoxyspergualin were necessary to cause inhibition of cell growth. When deoxyspergualin was added to the medium, there was a strong inhibition of cell growth and formation of active eukaryotic translation initiation factor 5A (eIF5A) at the third day of culture. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…To distinguish between these two options, we kept DFMO in the culture medium after the overlay of control cells to prevent polyamine synthesis (Figure 5C). Because control cells treated with DFMO generally continue dividing for at least 2 d in vitro (Nishimura et al , 2002), they have enough polyamines to trigger cell division of polyamine-depleted cells, and, indeed, we observed that the regrowth of polyamine-depleted cells was again detected (Figure 5C), although DFMO reduced the proportion of BrdU-positive cells of DFMO/APCHA-treated cells.…”
Section: Impaired Microtubule Dynamics and Maintenance Of Gap Junctiomentioning
confidence: 58%
“…To distinguish between these two options, we kept DFMO in the culture medium after the overlay of control cells to prevent polyamine synthesis (Figure 5C). Because control cells treated with DFMO generally continue dividing for at least 2 d in vitro (Nishimura et al , 2002), they have enough polyamines to trigger cell division of polyamine-depleted cells, and, indeed, we observed that the regrowth of polyamine-depleted cells was again detected (Figure 5C), although DFMO reduced the proportion of BrdU-positive cells of DFMO/APCHA-treated cells.…”
Section: Impaired Microtubule Dynamics and Maintenance Of Gap Junctiomentioning
confidence: 58%
“…3B), suggesting that DSG does not compromise the growth of the malaria parasite through inhibition of polyamine biosynthesis. DSG has earlier been demonstrated to inhibit formation of active eIF5A, which is generated by modification with hypusine, a derivative of spermidine, in mouse mammary carcinoma FM3A cells (40). However, the amount of hypusinated eIF5A in the malaria parasite was reduced only upon polyamine depletion at high micromolar concentrations of DSG (Fig.…”
Section: Effect Of Dsg On Polyamine Biosynthesis and Transport-mentioning
confidence: 90%
“…tion promoting greater vascularization around the cancer lesion and has also been found to protect cells from DNA-damaging agents and related apoptosis (Jeung et al, 2006). EIF5A1 (eukaryotic translation factor 1) has been shown to be involved in cell proliferation through the action of polyamines (Nishimura et al, 2002(Nishimura et al, , 2005, and plays a role in the regulation of TP53-related apoptosis (Li et al, 2004). PP1201, also known as transmembrane Bax inhibitor motif-containing 1 (TMBIM1), is a novel gene of cancer cells.…”
Section: Discussionmentioning
confidence: 99%